Design of silicon nitride metal-insulator-metal capacitor using 0.15 um gallium arsenide technology - Sanusi, Rasidah (2010)
Generally there are two groups of devices in GaAs technology, which are active and passive devices. Passive devices commonly used in GaAs are resistor, capacitor, inductor and transmission lines. This research work only focus on MIM capacitor device. The aim of this research work is to design and develop a model for Si3N4 MIM capacitor type which are fabricated on GaAs substrate so that they could be used in high frequency, as an example 2.4 GHz frequency (S band) of applications. Physical and electrical characteristics of the Si3N4 MIM capacitor devices for 0.15 μm GaAs technology are analyzed during layout design stage. 19 dimensions of Si3N4 MIM capacitor layout design are sent for fabrication. The fabricated devices are measured at frequency range between 0.1 to 20 GHz, and their electrical performances show some variation when compared to the simulation. Due to the variation of the devices, an equivalent circuit which represents the electrical performance of measured devices is introduced. Through tuning and optimization, model parameters of the equivalent circuit which fit to the measurement value was obtained.